Cuidados continuos. Una necesidad del paciente oncológico - Valentín, Vicente; Murillo, Mª Teresa; Valentín, María; Royo, Dolores (Psicooncología, 2004)
Continuity of care might be defined as an integral care to the patient as a whole: biological psychological social and the care of the family. That ´s why to get this global care, we need to care all the phases of the illness, since prevention and diagnosis, covering supportive care and reaching the palliative care when the cure is not possible and patients approach the end of life. Then, we need to apply the continuity of care along all the illness process in function of the needs and the resources and not only at the end of life.